Amplitude Calibration of the Tunka Radio Extension (Tunka-Rex). (July 2015) - Hiller, R; Bezyazeekov, P A; Budnev, N M; Gress, O A; Haungs, A; Huege, T; Kazarina, Y; Kleifges, M; Konstantinov, E N; Korosteleva, E E; Kostunin, D; Krömer, O; et al.
Abstract: Tunka-Rex is an experiment for the radio detection of cosmic-ray air showers in Siberia. It consists of 25 radio antennas, distributed over an area of 1 km 2 . It is co-located with Tunka-133, an air-Cherenkov detector for cosmic-ray air showers. Triggered by Tunka-133, Tunka-Rex records the radio signal, emitted by air showers with energies above 10 17 eV. Its goal is to probe the capabilities of a radio detector, especially for the determination of the energy and elemental composition of cosmic ray primaries. To compare the measurements of Tunka-Rex to other radio detectors or to models describing the radio emission, the radio signal in each station has to be reconstructed in terms of physical units. Therefore, all hardware components have to be calibrated. We show how the calibration is performed and compare it to simulations.